Influence of cover crop utilization on weed seed bank in soils of the Lerma Valley, Salta - Berruezo, Lorena Andrea; Toffoli, Lucia Mercedes; Harries, Eleonora; Plaza, Graciela Soledad; Chocobar, Mario Alejandro; Renfijes, Julio David; Mercado Cardenas, Guadalupe Eugenia (2026)
Resumen (en Ingles y Español) y Diapositivas